Penyimpangan Tender Proyek Pemerintah dan Relevansi Hifẓ al-Māl dalam Tata Kelola Pengadaan di Kabupaten Tolitoli - Eka Rizal; Muhammad Ali Rusdi; Nurdalia Bate (Tolis Ilmiah : Jurnal Penelitian, 2026)
Irregularities in government project tenders remain a serious problem because they cause financial losses to the state, reduce project quality, and weaken public trust in government institutions. This study aimed to analyze the forms of irregularities occurring in government project tenders in Tolitoli Regency and to examine the relevance of Hifẓ al-Māl to procurement governance. The study employed a descriptive-analytical qualitative approach with a normative-empirical paradigm. Data were collected through interviews, observations, and documentation involving 15 informants consisting of religious leaders, government officials, contractors, and community leaders. The data were analyzed using the interactive model of Miles and Huberman and a normative-theological approach based on the principles of maqāṣid al-syarī ah. The results showed that the dominant forms of irregularities included the predetermined selection of tender winners, personal relationships between officials and contractors, manipulation of administrative documents, lack of transparency, and delays and discrepancies in project implementation. All informants considered Hifẓ al-Māl to have strong relevance as an ethical foundation for tender governance because it regards public wealth as a trust that must be managed honestly, fairly, transparently, and responsibly. Therefore, the implementation of Hifẓ al-Māl may serve as a basis for strengthening the integrity of public officials, improving transparency, and preventing corruption, collusion, and abuse of authority in government project tenders.